Does Regional Development Influence Sedimentary Blue Carbon Stocks? A Case Study From Three Australian Estuaries - Conrad, Stephen; Brown, Dylan R.; Alvarez, Paula Gomez; Bates, Bronte; Ibrahim, Nizam; Reid, Alex; Monteiro, Luciana Silva; Silva, Daniela A.; Mamo, Lea T.; Bowtell, Jacob R.; Lin, Huang An; Tolentino, Nathaniel L.; et al. (Frontiers in Marine Science, 2019)
Mitigating climate change through the reduction of atmospheric CO2 levels is of interest, particularly through maintaining and re-establishing natural ecosystems that act as carbon sinks, such as coastal vegetated habitats or “blue carbon” systems. Here we compare sedimentary blue carbon (C) stocks from 37 sediment cores collected in pristine (n = 13), agricultural (n = 11), and urban (n = 13) estuaries within the same geomorphological region, located on the eastern coast of Australia. The mean estimated C stocks for each carbon system (seagrass, mangrove, and saltmarshes) were 402 ± 78, 830 ± 109, and 723 ± 100 Mg C ha-1, respectively, conservatively estimated up to 3 m depths. Analysis of variance revealed no significant difference between C stocks per area (C ha-1) considering each habitat type and between specific estuaries. However, the total estuarine C stocks were found to be greater with increasing levels of conservation, based on larger areas of blue carbon vegetation. The potential loss of C to the atmosphere from these small regional estuaries are 500,574 ± 118,635 tons of CO2 equivalent (CO2e), based on specific assumptions. The implication of these results are that there are large C stocks in small regional estuaries which supports the protection of blue C systems in developing coastal areas and highlights the uncertainties of the CO2 emissions from potential blue C habitat degradation.